2019
DOI: 10.3847/1538-4357/aafa7a
|View full text |Cite
|
Sign up to set email alerts
|

What is a Macrospicule?

Abstract: Macrospicules are typically described as solar jets that are larger and longer-lived than spicules, and visible mostly in transition-region spectral lines. They show a broad variation in properties, which pose substantial difficulties for their identification, modelling, and the understanding of their role in the mass and energy balance of the solar atmosphere. In this study, we focused on a sub-population of these jets that undergo parabolic trajectories when observed in the He II 304Å line using high-cadence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 108 publications
5
18
0
Order By: Relevance
“…Therefore, it is appropriate to compare our results with the properties of macrospicules, rather than those of spicules. Macrospicules are most often visible in EUV transitionregion lines, such as in He II 304Å, and consist of a cool core and hot sheath (e.g., Bohlin et al 1975;Withbroe et al 1976;Parenti et al 2002;Loboda & Bogachev 2019). Since the Mg II/304Å spicule has a cool component revealed in the Mg II image and a hotter component shown in the He II 304Å images, it has the typical properties of macrospicules described in the preceding papers.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, it is appropriate to compare our results with the properties of macrospicules, rather than those of spicules. Macrospicules are most often visible in EUV transitionregion lines, such as in He II 304Å, and consist of a cool core and hot sheath (e.g., Bohlin et al 1975;Withbroe et al 1976;Parenti et al 2002;Loboda & Bogachev 2019). Since the Mg II/304Å spicule has a cool component revealed in the Mg II image and a hotter component shown in the He II 304Å images, it has the typical properties of macrospicules described in the preceding papers.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, the fast wind, which does not exhibit strong FIP enhancements, could come directly from the photosphere, from small, cool coronal loops and open magnetic funnels at the base of coronal holes or spicules, which also exhibit small FIP enhancements. Remote observations have revealed many cases of macrospicules undergoing reconnection and erupting within coronal holes (Loboda & Bogachev 2019). Do they contribute to the fast solar wind streams?…”
Section: What Drives the Solar Wind And Where Does The Coronal Magnetmentioning
confidence: 99%
“…We use a higher velocity pulse to excite a faster jet and not let dissipation or numerical reflections dominate the system's evolution on timescales of interest and minimize numerical issues. Also, the initial amplitude of 100 km s −1 is the range of the average initial velocities from 70 to 140 km s −1 estimated by Loboda & Bogachev (2019) through a statistical analysis of macrospicule jets observed in coronal-holes and the quiet Sun.…”
Section: Perturbationmentioning
confidence: 99%
“…These giant spicules were introduced by Bohlin et al (1975), concerning the jets observed in Skylab's extreme ultraviolet (EUV) spectroheliograms at the solar limb. Besides, they are observed in polar coronal holes, where they reach heights from 7 to 70 Mm above the solar limb, maximum velocities from 10 to 150 km s −1 and lifetimes ranging from 3 to 45 minutes (Bohlin et al 1975;Withbroe et al 1976;Dere et al 1989;Karovska & Habbal 1994;Parenti, S. et al 2002;Bennett & Erdélyi 2015;Kiss et al 2017;Sterling 2000;Wilhelm 2000;Loboda & Bogachev 2019). In this context, a number of mechanisms have been proposed for the formation of macrospicules, for instance, by a pressure pulse (Hollweg 1982), through a velocity pulse (Suematsu et al 1982;Murawski et al 2011), magnetic recconection (Shibata 1982); among others (Moore et al 1977;De Pontieu et al 2004;Kamio et al 2010).…”
Section: Introductionmentioning
confidence: 99%